Feasibility of a Home-Based Therapeutic Exercise Program in Individuals With Knee Osteoarthritis - Cristina SILVA; António AMARO; António PINHO; Rui S. GONÇALVES; Mário RODRIGUES; Fernando RIBEIRO (Archives of Rheumatology, 2018)
Objectives: This study aims to evaluate the feasibility and potential benefits of a four-week home-based therapeutic exercise program for individuals with osteoarthritis (OA) of the knee. Patients and methods: Feasibility outcomes, namely the recruitment rate, retention rate, exercise adherence and adverse events, as well as pain, knee muscle strength, range of motion, functional mobility, physical function, and postural sway were assessed on 15 individuals (4 males, 11 females; mean age 62.8±2.5 years; range 55 to 83 years) with knee OA before and after a four-week home-based therapeutic exercise program. Results: The main results indicated that this program was feasible, as indicated by recruitment, adherence, and safety outcomes. The retention rate was 80% and the overall exercise adherence for those completing the program was 93%. The exercise program improved significantly pain intensity (visual analog scale: 5.8±2.8 to 3.8±2.4 cm, p=0.006), functional mobility, muscle strength, and physical function (Knee injury and OA Outcome Score-Physical Function Short-form: 53.8±21.0 to 41.3±13.9 points, p=0.011). Conclusion: This home-based therapeutic exercise program is feasible for individuals with OA of the knee and seems to improve pain intensity, functional mobility, muscle strength, and physical function.